ANALISIS PENGARUH RESTRUKTURISASI HUTANG TERHADAP RETURN SAHAM PADA PERUSAHAAN GO PUBLIK DI BURSA EFEK JAKARTA YANG MELAKUKAN RESTRUKTURISASI PADA TAHUN 2003 - Yulazri, Yulazri (Jurnal Ekonomi : Journal of Economic, 2017)
This research objective is to analysis the influence of debt restructuring of listed companies announcement to stock return. The influence of debt restructuring announcement to stock return shows where there is abnormal return which calculated by market model approach. This research based on the secondary data and the object of this research are listed companies at Jakarta Stock Exchange where their restructured their debts on the year 2003. Data collections covering : date of restructuring announcements (event date), daily stock price movement, daily composite index movement. The research methodology utilized is event study with estimation period 15 days and window period 31 days: 15 days before announcement date, at announcement date, 15 days after announcement date. Calculating abnormal return based on market model approach. Significant test of average abnormal return used one sample test at level of significantly of 5% performanced. The result of this research shows that debt restructuring announcement have influence to stock return, this indicated, there is abnormal return around date of debt restructuring announcement. Positive significant average abnormal return (AAR) occurred at day t+1, but at days t+2 also have negative significant average abnormal return (AAR), and the otherside the resulted of cumulative average abnormal return (CAAR) is negative. Strong and weak fluctuation of significant average abnormal return (AAR) have occurred at the period t-7 up to t+7. The trend of strong and weak of average abnormal return (AAR) at period t-7 up to t+7 with same model, 2 days with strong trend and then in the following day has more significant weakneses.Â Keywords : restructuring, event study, abnormal return